Особенности перевода имен собственных в произведениях жанра фэнтези - Кравченко, А.А.; Лукинова, М.Ю. (Культура народов Причерноморья, 2014)
Статья посвящена особенностям передачи имен собственных в произведениях жанра
фэнтези на другие языки на материале романов цикла “Discworld” Терри Пратчетта и их русских и
немецких переводов.
В статье определены особенности ономастикона (совокупности имен собственных) фэнтези-
произведений. Была проведена классификация способов передачи имен собственных на другие языки,
включившая транскрипцию, транслитерацию, транслокацию, транспозицию, калькирование, а также
комбинированные техники перевода. Кроме того, было проанализировано, какие способы передачи имен
собственных на другие языки преобладают при переводе на русский, а какие – при переводе на немецкий. Стаття присвячена особливостям передачі власних імен у творах жанру фентезі іншими
мовами на матеріалі романів циклу “Discworld” Террі Пратчетта і їх російсько- і німецькомовних
перекладів.
В статті виявлено особливості ономастікону (сукупності власних імен) фентезійних творів. Проведено
класифікацію засобів передачі власних імен іншими мовами, до якої увійшли транскрипція,
транслітерація, транслокація, транспозиція, калькування, а також комбіновані перекладацькі техніки.
Окрім того, було проаналізовано, які засоби передачі власних імен іншими мовами переважають під час
перекладу російською, а які – німецькою мовами. The article is devoted to peculiarities of rendering proper names in fantasy works into other
languages using the example of Terry Pratchett’s “Discworld” novels and their Russian and German
translations.
In the article the specific features of fantasy works and their onomasticon (all proper names) are defined. The
popularity of the genre, the increasing interest in western works of the kind, and, therefore, the necessity of
fantasy works translations are proved. The importance of adequate proper names translation (in this particular
case – rendering) is stated. Ways of rendering proper names into other languages that included transcription,
transliteration, translocation, transposition, loan translation and also combined translation techniques are
classified. The comparative analysis of translations of proper names into languages under consideration from
the English source language in Terry Pratchett’s works is carried out. Besides, it is analysed which ways of
rendering proper names prevail while translating into Russian and which – into German. The most important
factors that influence the translator’s choice of ways of rendering of proper names, the factors that are essential
for interpreting are enumerated. Strategies of translation of onomastic space of English fantasy works into
kindred (Russian) and sister, particularly German, languages are exploited and put in order.